Dilema Euthyphro dan Dasar Moralitas: Apakah Kebaikan Bergantung pada Perintah Tuhan? - Adelmi Kurniawati Ds; Olin Harun; Usman Pakaya (Pusat Riset dan Inovasi Nasional, 2025)
The Euthyphro Dilemma remains central to contemporary debates about the grounding of morality: are actions good because God commands them, or does God command them because they are good? This article reconstructs the main arguments in the dilemma, critically evaluates Divine Command Theory (DCT) and its variants (especially modified DCT) in comparison with non-theistic moral realism, and connects the debate to the need for public justification of norms in plural educational and cultural contexts. Using qualitative library research and philosophical–conceptual analysis (conceptual analysis, argument reconstruction, and critical normative appraisal), the study finds that strong DCT provides a straightforward account of the bindingness of obligation but faces the arbitrariness objection. Modified DCT mitigates arbitrariness by grounding commands in God’s good nature, yet it inherits challenges of circularity and limited public justificatory reach. The article proposes a layered justification model: theistic reasons may operate as internal motivational grounds for character formation, while institutional norms in education should also be supported by reasons accessible across diverse worldviews. This is aligned with Indonesia’s educational aims that combine faith/virtue and critical reasoning in the 8 dimensions of graduation profile.